2007
DOI: 10.1007/s10641-007-9241-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative feeding ecology of four sympatric skate species off central California, USA

Abstract: The big (Raja binoculata), California (R. inornata), longnose (R. rhina), and sandpaper (Bathyraja kincaidii), skates are commonly found on soft-bottom regions of the central California continental shelf and upper slope. The feeding ecology of this assemblage was compared to evaluate the degree of trophic separation among species, based on the results of previous speciesspecific diet studies. Specimens were collected from fishery independent trawl surveys conducted during September 2002-March 2003 at depths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 71 publications
3
95
0
2
Order By: Relevance
“…On the CS, diet overlap was biologically significant among all the batoid species, except M. aquila, and between the skate R. clavata and the shark S. canicula. The lack of significant dietary differences among comparably-sized shelf skates suggests that inter-specific resource competition was not intense (Bizzarro et al, 2007). High values of overlap do not necessarily imply competition, except when resources are in short supply (Macpherson, 1977;Cartes, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…On the CS, diet overlap was biologically significant among all the batoid species, except M. aquila, and between the skate R. clavata and the shark S. canicula. The lack of significant dietary differences among comparably-sized shelf skates suggests that inter-specific resource competition was not intense (Bizzarro et al, 2007). High values of overlap do not necessarily imply competition, except when resources are in short supply (Macpherson, 1977;Cartes, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Prey species were grouped by family and cumulative prey curves (CPCs) were created a posteriori to determine whether the sample sizes were sufficiently large to be used to describe prey abundance in both port locations. The CPCs were built by randomly resampling the stomachs 1000 times (Bizzarro et al, 2007) and plotting the mean cumulative number of identified taxa against the number of stomachs sampled (Ferry and Cailliet, 1996 …”
Section: Methodsmentioning
confidence: 99%
“…), and used to calculate a mean and standard deviation estimate for each sample (Colwell 2009). Linear regression was used to determine quantitatively whether the curve reached an asymptote, signifying an adequate number of samples (Bizzarro et al 2007b).…”
Section: Artisanal Fishery Surveymentioning
confidence: 99%